Outside options drive wage inequalities in continuing jobs: Evidence from a natural experiment - Veronika Lukesch; Thomas Zwick (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
The literature on wage bargaining so far mainly argues that unemployment benefits are relevant outside options for employees. This paper demonstrates that also a change in outside wage options drives wages in continuing jobs. The authors use the natural experiment of a crafts reform that reduces outside wage options for a clearly defined treatment group of employees in deregulated crafts occupations in comparison to employees in crafts occupations that have not been reformed. Five years after the reform, the wages of employees in deregulated crafts increased by five percent less than wages of employees in the other group. Reform effects are concentrated in employers with high increases in their median wage level after the reform. Wage differences therefore seem to be the result of wage renegotiations initiated by employees, rather than renegotiations initiated by employers. Works councils or collective bargaining, firm size, firm profits or regional unemployment have no impact on wage differetiation after taking wage increases into account. They show for the first time that changes in outside options induce wage differentiation at the employer level even in the tightly regulated German labour market. They use entropy matching on the basis of a large representative administrative linked employer-employee panel data set to guarantee homogeneous treatment and control groups before the reform. They isolate the outside wage option effect from other wage determinants by restricting our sample to employers not affected by the crafts reform.
Keywords: J24; J31; J44; L11; 330; wage bargaining; outside options; diff-in-diff estimation; matching